The Use of Pecha Kucha for Speaking English by Students Participating in Pecha Kucha Competitions (RETAIN, 2022)
Pecha Kucha is one of the styles of presentation that gives a new dimension of conventional presentation which is long, wordy, and boring. The researcher still do not know how the participants of Pecha Kucha competition make use of Pecha Kucha for learning to speak English. This study will investigate The Use of Pecha for Speaking English by Students Participating in Pecha Kucha Competition. This research is case study. The researcher used Qualitative method to analyze data. The subjects of this study were 15 participants who join National Pecha Kucha Competitions in 2017 and 2019 which is conducted by Lembaga Bahasa LIA. All participants were Senior High School student at that time. The data were collected through questionnaire on how students make use of Pecha Kucha and the speaking skills that they have learned by using Pecha Kucha. The questionnaire was followed by an interview session to get the deeper information about the questions in questionnaire. However, from the questionnaire followed by interview, the researcher found that participants make use of Pecha Kucha for speaking English starting from make an outline, script & get correction, and practice until the day of competition. They also learned five components of speaking skills from Pecha Kucha namely, pronunciation, grammar, fluency, and expression, and also participant added one component of speaking skill which is vocabulary. To summarize, the finding of this study showed that Pecha Kucha helps participants speaking English starting from preparing materials until delivering the presentation to engage the audience.